Electrochemical methods for on-site multidrug detection at festivals. Issue 4 (6th June 2022) - Van Echelpoel, Robin; Schram, Jonas; Parrilla, Marc; Daems, Devin; Slosse, Amorn; Van Durme, Filip; De Wael, Karolien
Abstract : Two electrochemical methodologies, i.e. flowchart and dual-sensor, were developed to aid law enforcement present at festivals to obtain a rapid indication of the presence of four illicit drugs in suspicious samples encountered. Abstract : Music festivals have emerged as an important setting for the consumption of illicit drugs, harming both consumers and society. Therefore, law enforcement present at these events requires straightforward, robust and accurate screening tools to obtain a rapid indication of the presence of these drugs in suspicious samples encountered on-site. Electrochemical profile (EP)-based drug sensing has proven to offer the desired affordability, portability and high-performance for this purpose. However, previous studies have mainly focused on the detection of only one drug type, rather than the simultaneous detection of multiple drugs. In this work, two innovative electrochemical methods ( i.e. the flowchart and dual-sensor) towards the rapid and accurate detection of the four main illicit drugs encountered at festivals (cocaine, 3, 4-methylenedioxymethamphetamine -MDMA-, amphetamine and ketamine) are developed and assessed based on their practicality, performance and limitations. The flowchart method employs sequential measurements in different measuring conditions, following a flowchart, combining good practicality, affordability and performance. The dual-sensor method combines the EP recorded in parallel at two electrodes with different measuring conditions into a superprofile. As the combined electrochemical information of the recorded EPs provides an increased selectivity, this method obtains the highest accuracy (87.5% vs. 80.0% for the flowchart) when applied to a set of confiscated samples. Interestingly, both methods outperform a portable Raman device (60%) that analyzed the same set of confiscated samples. Overall, these electrochemical methods offer law enforcement a rapid, portable and accurate screening method for the analysis of the large variety of suspicious samples encountered at music festivals.